Longitudinal examination of changing fertility intentions and behaviors over a four-year period in urban Senegal - Ilene S. Speizer; Veronica Escamilla; Peter M. Lance; David K. Guilkey (BMC, 2020)
Abstract Background Fertility intentions and contraceptive use are often used to demonstrate gaps in programs and policies to meet the contraceptive needs of women and couples. Prior work demonstrated that fertility intentions are fluid and change over a woman's (or couple's) life course with changing marital status, childbearing, and education/employment opportunities. This study uses longitudinal data to better examine the fluidity of women's fertility intentions and disentangle the complex interrelationships between fertility and contraceptive use. Methods Using survey data from three time points and three urban sites in Senegal, this study examines how women's fertility intentions and contraceptive use in an earlier period affect pregnancy experience and the intentionality of experienced pregnancies among a sample of 1050 women who were in union at all three time points. We apply correlated random effect longitudinal regression methods to predict a subsequent birth by fertility intentions and modern contraceptive use at an earlier period addressing endogeneity concerns of earlier analyses that only include two time periods. Results Descriptive results demonstrate some change in fertility desires over time such that 6-8% of women who reported their pregnancy as intended (i.e., wanted to get pregnant at time of pregnancy) reported earlier that they did not want any(more) children. Multivariate analyses demonstrate that women who want to delay or avoid a pregnancy and are using modern contraception are the least likely to get pregnant. Among women who became pregnant, the only factor differentiating whether the pregnancy is reported as intended or unintended (mistimed or unwanted) was prior fertility intention. Women who wanted to delay a pregnancy previously were more likely to report the pregnancy as unintended compared to women who wanted to get pregnant soon. Conclusions These results suggest some post-hoc rationalization among women who are getting pregnant. Women who say they do not want to get pregnant may be choosing not to use a contraceptive method in this urban Senegal context of high fertility. Programs seeking to reach these women need to consider their complex situations including their fertility intentions, family planning use, and the community norms within which they are reporting these intentions and behaviors.